Cationic nanoparticles loaded with prostaglandins and preparation method and application thereof
By modifying the quaternized chitin oligosaccharide on the surface of lignin nanoparticles, the prostaglandin-loaded cationic nanoparticles are formed, which solves the problems of poor water solubility of prostaglandins and the ocular surface barrier, and achieves the therapeutic effect of efficient intraocular pressure reduction and long retention effect.
Patent Information
- Application Number
- CN202510066639.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-08
AI Technical Summary
In the prior art, the water solubility of prostaglandins is poor, and there are multiple barriers on the eye surface, which leads to insufficient bioavailability of eye drops, making it difficult to achieve efficient treatment effect of lowering intraocular pressure.
Prostaglandin-loaded lignin nanoparticles were prepared by nanoprecipitation method, and quaternized chitin oligosaccharides or their derivatives were modified on the surface by electrostatic action to form prostaglandin-loaded cationic nanoparticles.
It achieves efficient delivery of prostaglandins, extends the ocular surface retention time, enhances corneal penetration ability, and significantly improves the efficacy of reducing intraocular pressure.
Smart Images

Figure CN119770671A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomedical materials, and in particular to a prostaglandin-loaded cationic nanoparticle and a preparation method and application thereof. Background Art
[0002] Glaucoma is a progressive optic neuropathy characterized by retinal ganglion cell degeneration and optic nerve damage. It is the leading cause of irreversible blindness worldwide. The death of ganglion cells is related to the degree of increase in intraocular pressure. Currently, lowering intraocular pressure remains the only effective way to treat the disease. Topical eye drops are convenient, non-invasive and low-cost, so they remain the main treatment. Among them, prostaglandins are a commonly used clinical ocular hypotensive drug, including latanoprost, bimatoprost, travoprost and tafluprost. For example, latanoprost (Lat) is a prostaglandin F 2α Analogues are commercial ocular hypotensive drugs currently used in the first line of clinical practice. They can selectively stimulate prostaglandin FP receptors, relax the ciliary muscle gap and promote the outflow of aqueous humor through the uveoscleral pathway to reduce intraocular pressure. However, they are poorly water-soluble; at the same time, due to the static and dynamic barriers on the ocular surface, such as tear circulation, nasolacrimal duct drainage, blink reflex, efflux transporters and corneal barrier effects, the bioavailability of eye drops is usually less than 5%. Therefore, it is very necessary to design a glaucoma eye drop that can overcome multiple barriers on the ocular surface and achieve efficient ocular hypotensive efficacy.
[0003] In recent years, nanotechnology has developed rapidly in the field of medicine, and various nanoformulations such as nanocapsules, nanomicelles, metal nanoparticles, and liposomes have been widely used in the field of ophthalmology. Nanoparticles are widely used in ophthalmology due to their small particle size and easy surface functionalization. Among them, nanoparticles based on natural products have attracted widespread attention due to their wide sources, low prices, renewability, good biodegradability and biocompatibility. Lignin (Lig) is an aromatic organic macromolecular compound and an important component of plant cell walls. Its content is second only to cellulose. In the papermaking industry, 50 million tons of lignin are produced each year, but less than 2% is effectively utilized. In recent years, lignin has received widespread attention in the field of biomedicine due to its renewability, low cytotoxicity, chemical modifiability and biological activity (antioxidant, antibacterial and UV protection). However, there are few reports on the application of lignin nanoparticles in the eye. Lignin nanoparticles are expected to load lipophilic prostaglandin anti-ocular pressure drugs through hydrophobic-hydrophobic interactions, thereby improving their solubility. Summary of the invention
[0004] In order to solve the poor water solubility of prostaglandins in the prior art; at the same time, due to the technical defects of static and dynamic barriers on the ocular surface, such as tear circulation, nasolacrimal duct drainage, blink reflex, efflux transporters and corneal barrier function, the present invention provides a cationic nanoparticle loaded with prostaglandins and a preparation method and application thereof, which are used for the efficient delivery of prostaglandins to achieve better intraocular pressure control, and further achieve the effect of long-term ocular surface retention and corneal penetration.
[0005] The technical solution adopted by the present invention is: a cationic nanoparticle loaded with prostaglandin, wherein the cationic nanoparticle loaded with prostaglandin is a prostaglandin-loaded lignin nanoparticle whose surface is modified with chitosan oligosaccharide or its derivative.
[0006] Preferably, the chitosan oligosaccharide or its derivative is quaternized chitosan oligosaccharide QCOS or its derivative.
[0007] Preferably, the quaternized chitosan oligosaccharide QCOS is modified on the surface of lignin nanoparticles through electrostatic action.
[0008] Preferably, the prostaglandin is one or more of latanoprost, bimatoprost, travoprost or tafluprost.
[0009] A method for preparing cationic nanoparticles loaded with prostaglandins comprises the following steps: (1) Synthesis of quaternized chitosan oligosaccharide QCOS: Weigh chitosan oligosaccharide, add deionized water to it, add glacial acetic acid while stirring, add 2,3-epoxypropyltrimethylammonium chloride GTMAC after reaction, transfer to an oil bath for reaction, centrifuge at room temperature, discard the precipitate, filter the supernatant, drop the filtered liquid into a mixed solution of anhydrous ethanol: acetone, centrifuge, take the precipitate, dialyze it with deionized water for 3 days, and freeze-dry to obtain the product; (2) Synthesis of lignin nanoparticles loaded with prostaglandins: Weigh prostaglandins and dissolve them in acetonitrile to form a mother liquor, and sonicate until they are completely dissolved. Weigh alkali lignin and add tetrahydrofuran, add the prostaglandin mother liquor and sonicate, slowly drop the above mixed solution into water, stir rapidly at room temperature, and transfer the mixed solution to a 3.5 KDa dialysis bag for dialysis. Then centrifuge to remove the precipitate to obtain lignin nanoparticles loaded with prostaglandins; (3) Synthesis of quaternary ammonium chitosan oligosaccharide QCOS-modified prostaglandin-loaded lignin nanoparticles: The QCOS solution was slowly added dropwise to the prostaglandin-loaded lignin nanoparticle solution, and then stirred and ultrasonicated to obtain QCOS-modified prostaglandin-loaded lignin nanoparticles.
[0010] Preferably, in the step (1), the speed of the reaction in the oil bath is 2000-10000 rpm, and the reaction time is 12-24 h.
[0011] Preferably, in step (2), the mass ratio of prostaglandin to lignin is 1:20 to 1:5.
[0012] Preferably, in step (3), the mass ratio of QCOS to drug-loaded lignin nanoparticles is 1:3 to 1:1.
[0013] Application of cationic nanoparticles loaded with prostaglandins in the preparation of drugs for treating glaucoma.
[0014] An eye drop for treating glaucoma, comprising the cationic nanoparticles loaded with prostaglandin.
[0015] The beneficial effects of the present invention are: cationic nanoparticles loaded with prostaglandins, and preparation methods and applications thereof, prostaglandin-loaded lignin nanoparticles are prepared by a nanoprecipitation method, chitosan oligosaccharides or their derivatives are modified on the surface by electrostatic action, the particle size and surface charge of the nanoparticles are studied in detail by DLS, the low cytotoxicity of the nanoparticles is confirmed by the CCK-8 method, and its good in vivo safety is further verified by eye drops in animals for 14 days, and it is also verified that the cationic nanoparticles can prolong the ocular surface retention time of the model drug and can reduce the expression of ZO-1. In the dexamethasone-induced high intraocular pressure model, the drug-loaded cationic nano eye drops achieve an intraocular pressure-lowering effect that is superior to naked drugs and anionic nano drugs. These nanoparticles are a new carrier for efficient ocular drug delivery with both long ocular surface retention and ocular surface penetration. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Schematic diagram of cationic prostaglandin nanoparticle eye drops improving the intraocular pressure-lowering efficacy.
[0017] Figure 2 a) Particle size of blank Lig, Lig-QCOS and drug-loaded Lat@Lig, Lat@Lig-QCOS nanoparticles; b) potential data; c) Tyndall effect of Lat@Lig-QCOS nanoparticles.
[0018] Figure 3 The zeta potential change after nanoparticles were co-incubated with mucin.
[0019] Figure 4 These are the in vivo fluorescence imaging results of free coumarin-6 (Co6), coumarin-6-loaded Co6@Lig and Co6@Lig-QCOS nanoparticles on the mouse ocular surface at different time intervals.
[0020] Figure 5a) Representative images of ZO-1 fluorescence staining of corneal tissue of normal SD rats 1 hour after eye drops with different materials; b) Comparison of quantitative results of ZO-1 fluorescence intensity among groups.
[0021] Figure 6 The survival rate of HCECs after incubation with different concentrations of Lig or Lig-QCOS nanocarriers for a) 24 h; b) 48 h. Figure 7 a) IOP-lowering effects of different latanoprost preparations; b) Numerical statistics of the area under the curve of each treatment group in the IOP-lowering experiment.
[0022] Figure 8 To investigate the animal safety of nano-drug carriers, the ocular surface of mice was examined after continuous eye drops of PBS, Lig, and Lig-QCOS blank nano-carrier materials for 1 and 2 weeks. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1 Synthesis of cationic nanoparticles loaded with prostaglandins Synthesis of Quaternary Ammonium Chitosan Oligosaccharide QCOS Weigh 1 g of chitosan oligosaccharide, add 30-50 mL of deionized water, add 180 μL of glacial acetic acid while stirring, react for 1 h, add 2 g of 2,3-epoxypropyltrimethylammonium chloride GTMAC, transfer to a 55°C oil bath, 8000 rpm, and react for 18 h. Centrifuge at room temperature, discard the precipitate, and filter the supernatant with a Buchner funnel. Drop the filtered liquid into an anhydrous ethanol / acetone mixed solution, centrifuge, take the precipitate, dialyze it with deionized water for 3 days, and freeze-dry to obtain the product.
[0025] Synthesis of Lat@Lig Weigh Latanoprost and dissolve it in acetonitrile to make a mother solution (5 mg / mL), and sonicate for 5 min until it is completely dissolved. Weigh 20 mg of alkali lignin, add 2.6 mL of tetrahydrofuran, add 0.4 mL of latanoprost mother solution, and sonicate for 10 min. Slowly add the above mixed solution dropwise to 7 mL of water and stir rapidly at room temperature for 2 h. Transfer the mixed solution to a 3.5 KDa dialysis bag and dialyze for 2 days. Then centrifuge at 4000 rpm in a centrifuge for 10 min to remove the precipitate to obtain latanoprost-loaded lignin nanoparticles Lat@Lig. Synthesis of Lat@Lig-QCOS The QCOS solution was slowly added dropwise to the Lat@Lig solution, and after stirring and ultrasonication, QCOS-modified Lat@Lig-QCOS nanoparticles were obtained.
[0026] Particle size and potential of Lig, Lig-QCS, Lat@Lig, and Lat@Lig-QCOS Dynamic light scattering was used to measure the particle size, PDI and Zeta potential of Lig, Lig-QCOS, Lat@Lig and Lat@Lig-QCOS.
[0027] Example 2 Mucin Adhesion Test Due to tear washout on the ocular surface, the bioavailability of eye drops is usually very low, but nano eye drops with ocular surface adhesion function can prolong the retention time on the ocular surface. In vitro mucin adhesion experiments can verify the adhesion ability of nanoparticles. Nanoparticles with positive charges on the surface can produce charge interactions with anionic glycosylation regions on ocular surface mucins, which is manifested as changes in Zeta potential after co-incubation of the two. The specific experimental steps are as follows: prepare a 1 mg / mL porcine gastric mucin solution with deionized water, mix it with 0.5 mL of Lig or Lig-QCOS nanoparticles of different concentrations, incubate it in a constant temperature shaker at 37°C for 1 h, and measure the Zeta potential of the mixed solution.
[0028] Example 3 Cell viability detection (CCK-8 experiment) CCK-8 kit was used to detect cell viability and evaluate the cytotoxicity of the material to cells. The specific operation steps are as follows: 1) This experiment is divided into an experimental group and a Blank group. The cells are plated in a 96-well plate according to the cell plate method. The number of cells is about 8×10³ / well, the volume is 100 μL, and the cells are cultured in a constant temperature cell culture incubator at 37°C and 5% CO2 for 24 h until the cells are completely attached to the wall; 2) The cell culture medium in the 96-well plate is aspirated, and 100 μL of the culture medium solution containing the material is added to the well plate according to the experimental design (different concentration gradients are set: 150, 100, 50, 20 μg / mL). Place in a constant temperature incubator and culture for 24 and 48 h; 4) After the set time, remove the culture medium in each well, add 100 μL of cell culture medium containing 10% CCK-8 solution to each well under light-proof conditions, and incubate at 37°C for 1-2 h; 5) Use an enzyme marker to detect the absorbance of the 96-well plate at 450 nm; 6) Calculate the cell survival rate. Example 4 Construction and treatment of hormone-induced high intraocular pressure model in C57BL / 6 mice This experiment uses a dexamethasone-induced mouse glaucoma model. 1) Prepare 0.1% dexamethasone sodium phosphate solution. 2) Select 6-8 weeks, 20-25 g, female C57BL / 6 mice. 3) Dexamethasone sodium phosphate eye drops, 3 times a day in the morning, noon and evening, 10 μL per eye. 4) Measure intraocular pressure at 9 am, twice a week. Take 3 average values for each eye. 5) The model is considered successful when the intraocular pressure reaches 15 mmHg. The mice with high intraocular pressure were randomly divided into three groups and given Lat naked drug, Lat@Lig anionic nanodrug, and Lat@Lig-QCOS cationic nanodrug respectively. The intraocular pressure of mice was measured as 0 point before administration, and the intraocular pressure was tracked and measured at 1, 2, 3, 4, 6, 8, 10, and 12 h after administration to evaluate the intraocular pressure lowering efficacy of each group. Example 5 ZO-1 immunofluorescence staining The content of ZO-1 is an important indicator of whether the corneal epithelial cell gap is open. QCOS on the surface of Lig-QCOS nanoparticles can open the corneal epithelial gap and reduce the content of ZO-1. In this experiment, SD rats were selected and divided into 3 groups, namely PBS, Lig and Lig-QCOS. The experiment was started after 10 μL was dripped into each eye of each group. Half an hour after the eye drops, the rats were killed, and frozen sections were made after the eye cups were made. After washing with PBS for 3 times, the samples were blocked with 10% goat serum for 1 h, washed with PBS for 3 times, and incubated with 10 μL ZO-1 antibody in a 4°C refrigerator for 16 h. After washing with PBS for 3 times, 10 μL DAPI anti-fluorescence quencher was added and the samples were sealed. Example 6 Corneal Adhesion Experiment Prolonging the ocular surface retention time of eye drops can improve the bioavailability of drugs. The quaternary ammonium chitosan oligosaccharide with positive charge on the surface of Lig-QCOS nanoparticles can electrostatically interact with ocular surface mucin to prolong ocular surface retention.In order to analyze the adhesion ability of nanoparticles, coumarin-6 (Co-6) fluorescent dye was used as a model drug. Using a stereo fluorescence microscope, the residual fluorescence intensity on the ocular surface represented the corneal adhesion ability of the drug in vivo. The specific experimental steps are as follows: 1) Anesthetize with sodium pentobarbital. The mice were divided into free Co6 group, Co6@Lig group and Co6@Lig-QCOS group, with 4 mice in each group (Co6 concentration was 40 μg / mL), and the experiment was started after 10 μL of eye drops were added to each group. 2) The fluorescence intensity was detected at 0, 0.5, 1, 1.5, 2, 3, and 4 h. Example 7 Ocular Surface Biosafety The ocular surface safety of blank nanocarriers was investigated using C57BL / 6 mice. Inclusion criteria: Slit lamp examination showed no ocular surface infection and corneal and conjunctival inflammation, no old / new corneal leukoma, no corneal ulcers and other abnormalities. The mice were randomly divided into 3 groups, namely PBS group, Lig group, and Lig-QCOS group. The mice were given eye drops once a day, 10 μL each time, for 14 days. During this period, strict attention was paid to ocular surface hygiene. On days 0, 7, and 14, the ocular surface was evaluated under a slit lamp using bright field and cobalt blue light.
[0029] Experimental Results Particle size and Zeta potential of lignin nanoparticles and drug-loaded nanoparticles The hydrated particle size and Zeta potential of Lig, Lat@Lig, Lig-QCOS and Lat@Lig-QCOS were measured by dynamic light scattering (DLS). Figure 2 As shown in the figure, the average particle size of Lig is 200.8 nm, the PDI is 0.147, and the average potential is -30.0 mV; the average particle size of Lat@Lig is 199.7 nm, the PDI is 0.122, and the average potential is -32.1 mV; the average particle size of Lig-QCOS is 228.8 nm, the PDI is 0.116, and the average potential is 18.6 mV; the average particle size of Lat@Lig-QCOS is 225.6 nm, the PDI is 0.08, and the average potential is 21.5 mV. After adding positively charged QCOS, QCOS binds to the surface of negatively charged blank Lig or drug-loaded Lat@Lig lignin nanoparticles through electrostatic interaction, turning the potential of the nanoparticles from negative to positive, and the particle size also slightly increases. In addition, Lat@Lig-QCOS nanoparticles have obvious Tyndall effect, which further confirms the successful preparation of cationic nanomedicines. The adhesion ability of nanoparticles is verified by in vitro mucin adhesion experiments. The anionic residues of mucin include aspartic acid and glutamine residues, so they are negatively charged. Nanoparticles with positive surface charge can interact electrostatically with mucin to achieve ocular surface retention. After co-incubation of mucin and nanoparticles, the changes in their Zeta potential are measured. Figure 3As shown in the figure, positively charged Lig-QCOS can reverse the potential of mucin after co-incubation with mucin, and the potential gradually increases with the increase of nanoparticle concentration, indicating that QCOS on the surface of nanoparticles and mucin have charge interactions. In contrast, Lig nanoparticles with negative surface charge do not have much effect on the potential of mucin. In vivo corneal adhesion experiment In this experiment, the residual fluorescence intensity in front of the cornea represents the retention ability of nanoparticles in front of the cornea. Figure 4 The groups were coumarin-6 (Co6) bare drug group, Co6@Lig nanoparticles loaded with Co6, and Co6@Lig-QCOS nanoparticles loaded with Co6. After 90 minutes of eye drops, the corneal fluorescence of Co6@Lig nanoparticles was significantly weakened, while the Co6@Lig-QCOS nanoparticle group could maintain it for more than 120 minutes, effectively prolonging the ocular surface retention time. Corneal ZO-1 staining In this experiment, the fluorescence intensity of the tight junction protein ZO-1 was used to represent the degree of openness of the corneal epithelial cell gap. Figure 5 The mice were divided into PBS group, Lig group, and Lig-QCOS group. One hour after eye drops, the fluorescence intensity of the Lig-QCOS group was significantly weakened, while the fluorescence of the Lig group had no significant change compared with the PBS group. The above results indicate that QCOS can help open the intercellular spaces of the corneal epithelium and promote drug penetration. Cell biocompatibility In order to study the biosafety of nanocarriers, the biocompatibility of nanoparticles of different concentrations on corneal epithelial cells HCECs was evaluated by CCK-8 experiment. Figure 6As shown in the figure, when Lig and Lig-QCOS nanoparticles were co-incubated with cells for 24 and 48 h, the survival rate of HCECs was higher than 80% when the nanoparticle concentration was within 150 μg / mL, indicating that the nanoparticles had good biocompatibility. Verification of the IOP-lowering Efficacy in an Animal Model of Hypertension The IOP-lowering Efficacy of Lat@Lig-QCOS was evaluated using a dexamethasone-induced hormonal hypertensive model. The intraocular pressure of mice was measured before administration as the 0 point, and the intraocular pressure was measured at 1, 2, 3, 4, 6, 8, 10, and 12 h after administration. The intraocular pressure of the Lat bare drug group, the Lat@Lig nanodrug group, and the Lat@Lig-QCOS cationic nanodrug group continued to decrease after administration, reaching the lowest point at 3 h, but the Lat@Lig-QCOS cationic nanodrug group had the largest IOP-lowering amplitude, reaching 5.2 mmHg, which was significantly stronger than the Lat bare drug group and the Lat@Lig group. The Lat bare drug group recovered to the initial IOP state at 6 h, while Lat@Lig-QCOS could continue to lower IOP to 10 h. We then calculated the area under the curve (AUC) of the IOP-lowering efficacy. The absolute values of AUC for Lat, Lat@Lig and Lat@Lig-QCOS were 10.4, 19.6 and 32.3 mmHg•h, respectively. The AUC values of the Lig-QCS@Lat group were approximately 3 times and 1.6 times those of the Lat and Lat@Lig groups. Therefore, the Lat@Lig-QCOS cationic nanodrug has a significantly improved IOP-lowering efficacy. This should be because the modification of cationic QCOS can help nanoparticles achieve long-term retention on the ocular surface while opening the intercellular spaces of corneal epithelial cells, increasing the penetration of the drug. Anterior segment slit lamp examination and corneal sodium fluorescein staining evaluation By continuously using blank Lig and Lig-QCOS eye drops, normal mice were given eye drops for 14 days, and their ocular surface changes were observed on days 0, 7, and 14. Figure 8 As shown, after eye drops, there was no significant difference between the nanocarrier group and the PBS control group. There was no congestion, no attached scales, no foreign matter in the rat eyelid margin, no foreign matter, no new blood vessels and turbidity in the corneal tissue, no obvious sodium fluorescein staining, no ciliary congestion, and no corneal ulcer. The above results show that the Lig-QCOS nanocarrier material will not cause damage to the ocular surface and has good biosafety.
[0030] In summary, the present invention prepares prostaglandin-loaded lignin nanoparticles by nanoprecipitation, further modifies the surface with chitosan oligosaccharide or its derivatives by electrostatic action, and studies the size and surface charge of the nanoparticles in detail by DLS. The low cytotoxicity of the nanoparticles was confirmed by the CCK-8 method, and its good in vivo safety was further verified by eye drops in animals for 14 days. In animal experiments, the present invention also verifies that cationic nanoparticles can prolong the ocular surface retention time of model drugs and can reduce the expression of ZO-1. Furthermore, in the dexamethasone-induced high intraocular pressure model, the drug-loaded cationic nano eye drops achieved an intraocular pressure-lowering effect that was superior to that of naked drugs and anionic nano drugs. Therefore, these nanoparticles are a new carrier for efficient ocular drug delivery that has both long-term retention and ocular surface penetration.
[0031] Technical personnel should note that although the present invention has been explained through the above specific implementation methods, the inventive concept of the present invention is not limited thereto. Any improvement or variation based on the inventive concept belongs to the protection scope of this patent right.
[0032] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments and experimental examples. Any technical solution that follows the concept of the present invention is included in the protection scope of the present invention. It should be emphasized that for ordinary technicians in this technical field, without departing from the purpose and scope of the present invention, any modification or equivalent replacement should be regarded as part of the protection scope of the present invention.
Claims
1. A cationic nanoparticle loaded with prostaglandin, characterized in that: The cationic nanoparticles loaded with prostaglandins are lignin nanoparticles loaded with prostaglandins whose surfaces are modified with chitosan oligosaccharide or its derivatives.
2. The prostaglandin-loaded cationic nanoparticles according to claim 1, characterized in that: The chitosan oligosaccharide or its derivative is quaternized chitosan oligosaccharide QCOS or its derivative.
3. The prostaglandin-loaded cationic nanoparticles according to claim 2, characterized in that: The chitosan oligosaccharide or its derivative is modified on the surface of lignin nanoparticles through electrostatic action.
4. The prostaglandin-loaded cationic nanoparticles according to claim 1, characterized in that: The prostaglandin is one or more of latanoprost, bimatoprost, travoprost or tafluprost.
5. A method for preparing cationic nanoparticles loaded with prostaglandins according to claim 1, characterized in that: The following steps are involved: (1) Synthesis of quaternized chitosan oligosaccharide QCOS: Weigh chitosan oligosaccharide, add deionized water to it, add glacial acetic acid while stirring, add 2,3-epoxypropyltrimethylammonium chloride GTMAC after reaction, transfer to an oil bath for reaction, centrifuge at room temperature, discard the precipitate, filter the supernatant, drop the filtered liquid into an anhydrous ethanol / acetone mixed solution, centrifuge, take the precipitate, dialyze it with deionized water for 3 days, and freeze-dry to obtain the product; (2) Synthesis of lignin nanoparticles loaded with prostaglandins: Weigh prostaglandins and dissolve them in acetonitrile to form a mother liquor, and sonicate until it is completely dissolved. Weigh alkali lignin and add tetrahydrofuran, add the prostaglandin mother liquor and sonicate, slowly add the above mixed solution dropwise into water, stir rapidly at room temperature, and transfer the mixed solution to a 3.5 KDa dialysis bag for dialysis. Then centrifuge to remove the precipitate to obtain lignin nanoparticles loaded with prostaglandins; (3) Synthesis of quaternary ammonium chitosan oligosaccharide QCOS-modified prostaglandin-loaded lignin nanoparticles: The QCOS solution was slowly added dropwise to the prostaglandin-loaded lignin nanoparticle solution, and then stirred and ultrasonicated to obtain QCOS-modified prostaglandin-loaded lignin nanoparticles.
6. The preparation method according to claim 5, characterized in that In the step (1), the reaction is carried out in an oil bath at a speed of 2000-10000 rpm and a reaction time of 12-24 h.
7. The preparation method according to claim 5, characterized in that: In the step (2), the mass ratio of prostaglandin to lignin is 1:20 to 1:
5.
8. The preparation method according to claim 5, characterized in that: In the step (3), the mass ratio of QCOS to drug-loaded lignin nanoparticles is 1:3 to 1:
1.
9. Use of the prostaglandin-loaded cationic nanoparticles according to claim 1 in the preparation of a drug for treating glaucoma.
10. An eye drop for treating glaucoma, characterized in that: The eye drops contain the prostaglandin-loaded cationic nanoparticles according to claim 1.